DISIPLIN WARGA BELAJAR MENGIKUTI PROGRAM KESETARAAN PAKET B DI PKBM LANCANG KUNING PALAS KANAN KECAMATAN RUMBAI - Kiki Elviora Vrismatia Elviora Vrismatia; Jaspar Jas Jaspar Jas; Aswandi Bahar Aswandi Bahar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to determine the high discipline of the learners in the program equality Paket B at PKBM Lancang Kuning Palas Kecamatan Rumbai Pekanbaru. The question that guides this study is: how high the level of discipline in the learning community program equality Paket B at PKBM Lancang Kuning Palas Kecamatan Rumbai Pekanbaru?. This is a descriptive research, data was collected using a questionnaire instrument shaped 43 point statement. After tested, the questionnaire is valid as for 31 points, and is not valid as for 12 points. Overall the instrument is valid with